2005
DOI: 10.1111/j.1743-6109.2005.20230.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Inhibition of the Angiotensin-Converting Enzyme (ACE) on Cavernosal Perfusion in Men with Atherosclerotic Erectile Dysfunction: A Pilot Study

Abstract: Introduction Impaired perfusion of the corpora cavernosa is considered an important causal factor of erectile dysfunction (ED) in the aging male with atherosclerosis. Aim On the basis of this notion, we hypothesized that inhibition of angiotensin-converting enzyme (ACE) may have a structural beneficial effect on cavernosal perfusion and subsequently on erectile function in men with impaired cavernosal perfusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
(29 reference statements)
0
14
1
1
Order By: Relevance
“…In a separate studying comparing quinapril against placebo for the treatment of hypertensive men with atherosclerotic ED, researchers found that cavernosal perfusion significantly improved in both groups. This suggests a possible psychological component to the perceived improvement in erectile function in men who use ACE inhibitors 34. Overall, ACE inhibitors likely do not adversely affect erectile function and may improve function in men with metabolic syndrome and atherosclerotic ED.…”
Section: Antihypertensive Drugsmentioning
confidence: 96%
“…In a separate studying comparing quinapril against placebo for the treatment of hypertensive men with atherosclerotic ED, researchers found that cavernosal perfusion significantly improved in both groups. This suggests a possible psychological component to the perceived improvement in erectile function in men who use ACE inhibitors 34. Overall, ACE inhibitors likely do not adversely affect erectile function and may improve function in men with metabolic syndrome and atherosclerotic ED.…”
Section: Antihypertensive Drugsmentioning
confidence: 96%
“…Previously, we observed reduction of vascular oxidative stress and endothelial dysfunction with subsequent improvement of endothelial function of penile tissue in apolipoprotein‐E‐deficient (ApoE −/− ) treated with the AT 1 receptor antagonist irbesartan, which is in line with clinical findings of advantageous effects of AT 1 receptor blockade in hypertensive patients (Fogari et al ., 2001; Dusing, 2003; Baumhakel et al ., 2008). For reduction of Ang II formation via angiotensin converting enzyme (ACE) inhibitors, comparable effects have been described (Dorrance et al ., 2002; Speel et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators attributed these results to the reduction in the vasospastic effect and free radical generation by angiotensin II and to enhancement of endothelial NO production. Moreover, in a pilot study enalapril showed a positive effect on cavernosal perfusion and erectile function in middle aged patients with atherosclerotic ED (mean age 60 AE 6.8 years) (Speel et al, 2005). In a cross-over study, Fogari et al (2001) treated 160 hypertensive men without prior sexual dysfunction with carvedilol or valsartan; patients were divided in two groups and assumed placebo for 4 weeks, then carvedilol 50 mg/die or valsartan 80 mg/die for 16 weeks and then, after additional 4 weeks placebo step, switched to the other drug for 16 weeks.…”
Section: Pharmacological Treatment Of Heart Failure In Patients With Edmentioning
confidence: 95%